(3NWGjG GdCfHjGAs - (3jMji Hf GdMSfs ((3eMeO Hf YHO Gddg Hf GdMSjf s)
(3ChdgG (B:s
(3SFd GdgGOi Edi GdMb jMji Hf GdMSjf Yf bhd Gddg JHGQc hJYGdi (B( (3hEPG bdfG ddedGFcI GSLOhG dGOe aSLOhG EdG HdjS(B) (3cja cGf GdSLhO ef GdedGFcI s
(3BNQgG (B:s
(3Qhi Yf GdfHi Udi Gddg Ydjg hSde Gfg bGd (B( (3GddhM Yde Gddg hcQSjg Ydeg hGddhM Yde Gddg GdPi hSY cd TF YeG cGf Gh Sjchf Je cJGH NWGjG GdGfHjGA Ydjge GdSdGe hdG Mhd hdG bhg EdG HGddg GdYdi GdYXje s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3Gdjef s
Keywords: (3GdJUha hGdBOGH GdTQYjIs